Impact of Solar Radiation Effects on the Physicochemical Properties of Polyethylene (PE) Plastic Film. (3rd July 2015) - Adelhafidi, A.; Babaghayou, I.M.; Chabira, S.F.; Sebaa, M.
Abstract: This study deals with the photodegradation of polyethylene films for greenhouse covering. The UV range of solar light appears as the most deleterious factor of plastic degradation in outdoor exposure. The reasons of this photosensitivity are structural defects which are light absorbing. The use of FTIR as an investigation tools has revealed that the material reacts with surrounding oxygen via a photooxidation process. Although, the photochemical process is quite complex it appears through this study than crosslinking and chain scissions are the most important events taking place during ageing These two key reactions change irremediably the average molecular weight affecting thus drastically the mechanical properties and reducing in the same way the service life time of the films.